Basic aspects of musculoskeletal pain: from acute to chronic pain - Arendt-Nielsen, Lars (Maney Publishing, 2011)
The transition from acute to chronic musculoskeletal pain is not well understood. To understand this transition, it is important to know how peripheral and central sensitization are manifested and how they can be assessed. A variety of human pain biomarkers have been developed to quantify localized and widespread musculoskeletal pain. In addition, human surrogate models may be used to induce sensitization in otherwise healthy volunteers. Pain can arise from different musculoskeletal structures (e.g. muscles, joints, ligaments, or tendons), and differentiating the origin of pain from those different structures is a challenge. Tissue specific pain biomarkers can be used to tease these different aspects. Chronic musculoskeletal pain patients in general show signs of local/central sensitization and spread of pain to degrees which correlate to pain intensity and duration. From a management perspective, it is therefore highly important to reduce pain intensity and try to minimize the duration of pain.